Application of molecular dynamics simulation in food carbohydrate research-a review - Feng, T.; Li, M.; Zhou, J.; Zhuang, H.; Chen, F.; Ye, R.; Campanella, O.; Fang, Zhongxiang (Elsevier Ltd, 2014)
Molecular dynamics (MD) simulation is an emerging technique in studying the interactions between macromolecules with small ligands in different media. In this review, the application of MD simulation in food carbohydrate research, including carbohydrate hydration, carbohydrate interaction with other components and carbohydrate inclusion complexation, will be discussed. The advantages and disadvantages of MD simulation in food carbohydrate research and trends will be proposed. The frequently used software to run the MD simulation and a standard protocol for MD simulation procedures have been discussed. This review offers a general idea about how to use MD simulation in food carbohydrate research, and what could be expected from such research. Industrial relevance: This review offers a general idea about how to use MD simulation in food carbohydrate research, and what could be expected from such research. This review might be useful for the flavor and nutraceuticals encapsulation, dietary carbohydrate and modified starch industries.